Dose dependency of aliquot sizes and age models from modern alluvial fan deposits of Helan Mountain, China - Liu, Xiuying; Li, Xiao; Zhao, Qiuyue; Pan, Baolin; Wang, Junping; Wei, Mingjian (Frontiers in Earth Science, 2022)
Alluvial fan deposits are identified as evidence of regional climatic variations and tectonic events; therefore, it is crucial to establish absolute time series by dating alluvial fan deposits. Limited exposure to light poses a challenge to accurately estimate the buried ages for alluvial deposits with optically stimulated luminescence (OSL). This challenge has been positively developed by controlling the number of grains on each disk to measure and choosing suitable statistical models for the equivalence dose (De) distribution to analyze. In this research, three modern alluvial samples and one modern loess-like sample were collected from the Dashuigou (DSG) alluvial fan of Helan Mountain, China. The De distributions of these four samples were studied by the application of small aliquots (1 mm, 3 mm and 5 mm aliquots) of quartz OSL with the average dose model (ADM), central age model (CAM), unlogged minimum age model (MAM), lowest 5%, internal/external consistency criterion minimum age model (IEU) and finite mixture model (FMM). It is concluded that an overestimation of De lower than 1 Gy can be obtained using quartz OSL dating of 1 mm aliquots (~ 50 grains) with MAM and IEU for the alluvial sediments. The lowest 5% method may underestimate the De values of the 1 mm aliquots for young samples. This research makes the dose dependency of aliquot sizes and age models more definite and opens up the possibility of dating paleoalluvial deposits to establish a chronological framework to decipher the implications of paleoclimates and tectonics.